Production of nanostructured molecular liquids by supercritical CO2 processing - Sudhir Kumar Sharma; Abiy D. Woldetsadik; Thomas Blanton; Matthew J. O'Connor; Mazin Magzoub; Ramesh Jagannathan (Elsevier, 2017)
Stable molecular clusters of ibuprofen and naproxen were prepared in dry ice, by supersonic jet expansion of their supercritical CO2 drug formulations into a liquid nitrogen cooled collection vessel, with up to 80% yield. Mixing the "dry ice" in water, resulted in the solubilization of the clusters and in the case of ibuprofen, we were able to create solutions, with concentrations of up to 6 mg/ml, a 300-fold increase over previously reported values. Drop casting and ambient drying of these solutions on silicon substrate resulted in a stable, viscous liquid film, referred to as nanostructured molecular liquids. These liquids exhibited a highly aligned, fine (self-assembled) super lattice features. In vitro cancer cell viability studies of these formulations exhibited similar cytotoxicity to that of the original raw materials, thus retaining their original potency. Besides its scientific importance, this invention is expected to open up new drug delivery platforms.